Self-association promoted conformational transition of (3R,4S,8R,9R)-9-[(3,5-bis(trifluoromethyl)phenyl))-thiourea](9-deoxy)-epi-cinchonine - Király, Péter (Magnetic resonance in chemistry : MRC, 2010)
Copyright 2009 John Wiley & Sons, Ltd.